A novel ultra-high temperature ceramic composite coating prepared by high-speed laser cladding and pack cementation on Ta–W alloys for higher plasma ablation resistance above 2300 °C - Youjiang Zhang; Qiyao Deng; Yang Li; Pengfei He; Chuan Sun; Wengang Bu; Yue Xing; Yujun Cai; Xiubing Liang (Journal of Advanced Ceramics)
To improve the high-temperature ablation resistance properties of Ta(W) refractory alloys, a novel ultra-high-temperature ceramic (UHTC) composite coating was prepared by combining the technological advantages of high-speed laser cladding (HSLC) and pack cementation (PC). First, the HSLC process was employed to fabricate a (Hf,Ta)C–Ta(W) UHTC–refractory metal composite coating that had metallurgical bonding with the Ta(W) substrate. Then, the PC process was utilized to transform the refractory metal phase in the coating into the corresponding refractory silicide (RMSi2) phase. Consequently, the (Hf,Ta)C–TaSi2 UHTC composite coating was successfully prepared. This new coating was ablated at a heat flux density of 8.0 MW/m2 for 300 s at a surface temperature of 2300 °C, and the structural integrity of the coating was retained. The linear ablation rate of the coating is −0.67 µm/s. The ablated coating exhibits three distinct oxide layers: a loose HfO2 top layer, a dense HfO2 middle layer, and a slightly oxidized (Hf,Ta)CxOy–Hf–Ta–O glassy layer. The synergistic effect of HfO2 and Hf–Ta–O glassy oxide film endows the coating with excellent anti-ablation resistance. This innovative design of the UHTC–RMSi2 composite coating provides robust protection to the Ta(W) substrate from ultra-high temperature ablation and mechanical scouring.